M38. PATIENT-PERSPECTIVE: NEED FOR CARE AFTER A FIRST PSYCHOSIS. (18th May 2020) - Heijden-Hobus, Inge; van der Heijden-Hobus, Inge; Rosema, Bram-Sieben; Vorstman, Jacob; Kas, Martien; Begemann, Marieke; Kikkert, Martijn; Sommer, Iris
Abstract: Background: Only little is information is available about the needs and preferences regarding care and treatment of people who are going through a psychosis for the first time. A first psychotic episode is often an intense experience, which may not directly be recognized as a mental health problem. Given the unfamiliarity with the available options of care, it probably differs from subsequent psychoses. In order to design first psychosis programs to optimally meet patients preferences, we need to learn the care needs of these usually young people. Furthermore, peoples' needs during the first psychosis, and the need for care after a psychotic episode have to be explored, in order to be able picking up life again after complete or incomplete remission. Methods: Qualitative interviews were conducted with people (n = 20) who are in complete or partial remission after their first psychosis about their personal care needs. Interviews were conducted by an experience expert and a researcher together and lasted between 1 and 3 hours. Interviews were non-structured, but a basic set of 5 topics was used. Results: Preliminary results of the interviews conducted so far (n = 14) show that people with a first psychosis have a great need for information about the symptoms they are suffering from. In addition, they believe that medication is an important 'cornerstone' to get rid of their symptoms. Furthermore, nearly all participants hope to be able to stop medication in the near future. Admission to a ward is in most cases experienced as frightening. One person indicated that the tranquility during admission was very welcome. At this stage, experience experts are not being reached out to yet, nor is there a clear need for social work in this stage of the disease. During and shortly after their first psychosis, the interviewees especially appreciate the support of family and close friends. Discussion: Clear information about a first psychosis was mentioned as the first need. Family and close friends are most appreciated as "auxiliary troops". Family support is therefore an important contributor in care for patients suffering from psychosis. Medication was appreciated as an important cornerstone, but only to induce remission, not as a mean for maintenance treatment. Admission was by most patients experienced as stressful. Additional research is recommended to further map what information this should be exactly, and how to bring it to the patient and his relatives.